ANALYZING THE SECOND YEAR STUDENTS’ DIFFICULTIES ON READING ANALYTICAL EXPOSITION TEXT AT SMA NEGERI 9 PEKANBARU - Nurul Aini Ibni Kalzan; Jismulatif; Atni Prawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research was aimed to find out students’ difficulties of on understanding analytical exposition texts. This was descriptive quantitative research. The population of this research was the second-year students at SMA Negeri 9 Pekanbaru, and one class at the second grade was chosen as the sample by using clustering-random-sampling. This research utilized a reading test and a questionnaire as the instruments. The results of this research revealed that students faced several difficulties to understand analytical exposition texts based on 8 indicators, namely finding the main idea, finding factual information, finding references and inferences, finding vocabulary, identifying the social function, identifying the generic structure, and identifying language features of the analytical exposition text. Moreover, it was found that students had difficulties in identifying the social function (56%) which was categorized as high, in identifying the generic structure (54%) which was categorized as medium, and in the language features of the text (54%) which was categorized as medium. Then, data from the questionnaire showed that students had problems in understanding the text, in reading interest, and the lack of material review. Thus, it was concluded that the second-year students at SMA Negeri 9 Pekanbaru had difficulties on reading analytical exposition text. It was recommended for the students to learn and practice more about analytical exposition text. Then, it was suggested for English teachers to give more detailed explanation and exercises about analytical exposition text. Keywords: , ,